Sistema web de gestión de procesos de la editorial Humus de la ESPAM MFL - Intriago Pico, Raquel Dolores (2023)
The objective of this curricular integration work was to develop a web system to facilitate the management of processes in the publication of books and news related to the Humus publishing house at ESPAM MFL. For this, the Extreme Programming agile methodology was applied, which has four phases: planning, design, coding and testing; in the planning phase, the compilation of the user stories and the definition of the requirements and software requirements was carried out, based on the IEEE 830 standard; in the design phase, the system interfaces and CRC cards were established; in the coding, the source code of the system was developed using the ASP.NET framework, the MVC architecture and the SQL SERVER database manager and finally, in the testing phase, the proper functioning of the system was verified through unit and acceptance tests. As a result, it was possible to verify the optimization of the management of the processes in the publication of books and book chapters of the Humus publishing house through the collaboration of a group of teachers who used the system to carry out the book publication processes.